Characteristics of Pterygium Patients at Waled Regional Hospital - Findi Amilia Sumarto; Viora Rianda Piscaloka; Widi Astuti (Journal La Medihealtico, 2026)
Pterygium is a triangular fibrovascular growth of the ocular surface that is commonly found in tropical regions, including Indonesia. This condition is frequently associated with prolonged ultraviolet exposure and may cause recurrent red eyes, irritation, foreign body sensation, and visual disturbance. This study aimed to describe the characteristics of pterygium patients at Waled Regional General Hospital, Cirebon Regency, in 2025, based on age, gender, occupation, duration of ultraviolet exposure, pterygium grade, and clinical manifestations. This study used a descriptive observational design with primary data collected through questionnaires. A total of 42 patients diagnosed with pterygium were selected using total sampling according to the inclusion criteria. The data were analyzed using univariate analysis and presented as frequency and percentage distributions. The results showed that most patients were aged 56–65 years (42.9%) and were female (61.9%). Housewives represented the largest occupational group (52.4%), and most respondents had ultraviolet exposure of more than five hours per day (76.2%). Grade II pterygium was the most common severity level (42.9%), while recurrent red eye was the most frequently reported clinical manifestation (42.9%). These findings indicate that pterygium patients at Waled Regional General Hospital were predominantly older adults, women, and individuals with prolonged ultraviolet exposure. Therefore, preventive education regarding eye protection, including the use of sunglasses, hats, or other protective equipment during outdoor activities, is essential to reduce the risk and progression of pterygium.